Measurements of Ions Emission Using Tof Method and cr39 Ssntd in a Small Plasma Focus Device of Hundreds of Joules - Pedreros, J (Institute of Physics Publishing, 2014)
Ion beam emission in plasma focus (PF) discharges was originally investigated to explain the strong forward anisotropy observed in the neutron emission when D2 is used as filling gas in the PF devices. Several properties of emitted deuteron beam, including its angular distribution and energy spectra in PF devices operating at energies from 1kJ to 1MJ, have been measured. At present there is a growing interest in the development of very small PF devices operating under 1kJ. As part of the very low energy (< 1kJ) PF devices physics characterization program carried out at the Chilean Nuclear Energy Commission, the charged particle emission is being studied when hydrogen (H2) and mixture (H2+ %Ar) is used as filling gas in the PF device. The experiments have been performed in a plasma focus device of 400 joules (PF-400J). In order to estimate the ion beam energy spectrum and its ionization degree, by means of the time of flight method, a graphite collector system operating in the bias ion collector mode was constructed. On the other hand, measurements of the energy and flux of the ions have been corroborated using CR39 SSNTD. Preliminary results mainly show the presence of hydrogen ions with an average energy of 40keV. Also, in some cases, copper (from anode) and aluminum (from insulator) ions with energies lower than 1keV have been observed.